Post-COVID fatigue: a new era of complication by altered thyroid function - Alam, Mohammad Masum; Rahman, Mohammad Matiur; Mollah, Forhadul Hoque; Chowdhury, Indira (BIRDEM Medical Journal, 2023)
Background: Since late 2019, the development of severe acute respiratory distress syndrome (SARS) occurred, which began as a small cluster of cases in Wuhan, China and subsequently spread across the globe in the shape of a global pandemic. Coronavirus disease 2019 (COVID-19) initiates an immune response over-activity leading to release of pro-inflammatory cytokines, particularly interleukin-6 (IL-6), which leads to overt thyroid dysfunction by disruption of thyroid transport proteins. Level of triiodothyronin (T3) is inversely proportional to IL-6 with a modest decrease of thyroid stimulating hormone (TSH) and thyrotropin (T4). Fatigue is usually expressed by lack of one or more of habits or routines, particularly a lack of exercise. It is also frequently associated with depression. Fatigue might be an indication of various underlying illnesses that necessitate medical attention. COVID-19-related thyroid disorders could biochemically manifest as thyrotoxicosis, hypothyroidism, as well as non-thyroidal illness syndrome. Post-COVID fatigue has become an alarming complication which remains undiagnosed causing more complication at later stage. There are very limited knowledge regarding altered thyroid function in patients who have recovered from COVID-19. Aims of this study were to know about the derangement of thyroid hormones. Methods: This cross-sectional study was conducted in the Department of Biochemistry and Molecular Biology, BSMMU, Dhaka from July, 2020 to June, 2021. A total of 100 post-COVID patients (age 18 – 70 years) with fatigue were enrolled for this study. Among them, 50 were treated at home and 50 were treated in hospital. For this study, serum TSH and FT4 were measured by the automated analyser. The data were expressed as frequency and percentage, mean for normally distributed data. p value d”0.05 was considered statistically significant. Results: The value of TSH and FT4 in home and hospital treated patients were 1.59, 2.96 mIU/L and 9.27, 17.28 pmol/L respectively. There was significant difference of level of serum TSH (p < 0.0001) and FT4 (p < 0.0001) between home and hospital treated post COVID-19 patients with fatigue. Conclusion: Home treated post-COVID patients with fatigue expressed higher level of serum TSH and FT4 than that of hospital treated patients. BIRDEM Med J 2023; 13(1): 34-37